Effect of different fining agents and additives in white wine protein stability - Ribeiro, Tânia Isabel Monteiro (2014)
One of the most common physical instability is the development of protein hazes in white wines. Bentonite (B) is widely used for the treatment of protein instability however in excess it adversely affects its sensorial properties. Thus, the main objective of this study was to compare the efficiency of different B and mannoproteins (MP) on removal protein hazes, and then developing new strategies for protein stabilization. Two tests have been used to assess the stability of wines: heat-test and TCA-test. The effects of treatments on phenolic compounds, chromatic and sensory characteristics of wines were evaluated. Results showed that both B and MP increased protein stability but, MP also improved the sensorial characteristics of wines, indicating that can be an alternative to stabilize wine proteins.